TYPES OF PHRASEOLOGISMS ACCORDING TO SEMANTIC CLASSIFICATION - Hojiyeva Gulchehra Salimovna; Olimova Madina (Western European Studies, 2025)
This article discusses the semantic classification of phraseologisms and their significance in linguistics. Phraseologisms are expressions that have a certain meaning, but when taken separately, the words in them do not express that meaning. The article analyzes the types of phraseologisms, their semantic properties and contexts of use. The article also examines the relationship between phraseologisms and language, their communicative functions and role in speech. Phraseologisms, along with ensuring the richness of the language, also reflect national culture and traditions. At the end of the article, recommendations are made for future research on the study of phraseologisms in linguistics and their application in practice. This article aims to provide a deeper understanding of the semantic classification of phraseologisms and their role in linguistics, and serves as a useful resource for researchers and linguists.
Keywords: Phraseological units; semantic classification; phraseological combinations